Branching Ionizable Lipids Can Enhance the Stability, Fusogenicity, and Functional Delivery of mRNA. Issue 1 (9th November 2022) - Hashiba, Kazuki; Sato, Yusuke; Taguchi, Masamitsu; Sakamoto, Sachiko; Otsu, Ayaka; Maeda, Yoshiki; Shishido, Takuya; Murakawa, Masao; Okazaki, Arimichi; Harashima, Hideyoshi
Abstract : Ionizable lipids with branched tails have been used in lipid nanoparticles (LNPs)‐based messenger RNA (mRNA) therapeutics like COVID‐19 vaccines. However, due to the limited commercial availability of branched ingredients, a systematic analysis of how the branched tails affect LNP quality has been lacking to date. Herein, α‐branched tail lipids are focused, as they can be synthesized from simple commercially available chemicals, and the length of each chain can be independently controlled. Furthermore, symmetry and total carbon number can be used to describe α‐branched tails, facilitating the design of a systematic lipid library to elucidate "structure–property–function" relationships. Consequently, a lipid library is developed containing 32 different types of α‐branched tails. This library is used to demonstrate that branched chains increase LNP microviscosity and headgroup ionization ability in an acidic environment, which in turn enhances the stability and in vivo efficacy of mRNA‐LNPs. Of the branched lipids, CL4F 8‐6 LNPs carrying Cas9 mRNA and sgRNA could achieve 54% genome editing and 77% protein reduction with a single dose of 2.5 mg kg −1 . This mechanism‐based data on branched lipids is expected to provide insights into rational lipid design and effective gene therapy in the future. Abstract : Branched‐tail lipids are commonly used for the delivery of messenger RNA (mRNA). However, the exact role of the branched chains remains unclear. To address this, a lipid library is developed containing 32 different types of α‐branched tails. This library enables a systematic comparison and demonstrates that branched chains can enhance the stability, fusogenicity, and functional delivery of mRNA.